Literature Review: Hubungan Penggunaan APD dengan Kejadian Penyakit Dermatitis pada Nelayan - Shelsi Yulia Astri; Nur Ainun Waruwu; Anissa Sabillah Hutasuhut; Chairul Imam; Reni Agustina Harahap (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Dermatitis is an infection that occurs on the skin which is characterized by red nodules and itching. Fishermen are one of the workers who are most likely to suffer from dermatitis. The purpose of this research is to analyze the relationship between the use of APD and the incidence of dermatitis experienced by fishermen due to work. The research method used is a literature review, which is a collection of several daily articles from 2018-2022 using the keywords "The impact of work with eczema on fishermen" and "Use of personal protective equipment by fishermen". Dermatitis is reddened skin and usually an itchy rash, which causes irritation after direct contact with sea water. Fishermen who wear head protective equipment while working are 62.4% and those who do not wear boots are 23.59%